PENGARUH BENTUK PENGARAH ANGIN (DEFLECTOR) TERHADAP KARAKTERISTIK AERODINAMIS KENDARAAN NIAGA (TRUCK) - Wahyudi, Wahyudi; Rubiono, Gatut; Mujianto, Haris (ROTOR, 2014)
Aerodynamic is a branch of science which study the effect of wind to an object. Transport vehicle (truck) is one of the object in this field. A deflector is use to direct the wind for aerodynamics aspect. The research is conduct in a small scale wind tunnel with 40 cm x 40 cm cross section and 300 cm length. A truck model is varied without deflector, flat deflector, convex deflector and concave delector. The wind speed is varied at 1,9; 2,31 and 3,23 m/s by a fan. U type manometers with 30o inclination are used to measure height difference (Dh) of the water column at 3 pointsabove the deflector. The data are used to count the wind pressure and the wind speed.Aerodynamic performance is described as a capability to maintain the wind speed at measurement points.The research result shows that the deflector has effect due to aerodynamics characteristic of truck model. Convex deflector has the best performance. Flat and concave deflectors are next. Â  Keywords: aerodynamics, truck, deflector